Purine‐related metabolites and their converting enzymes are altered in frontal, parietal and temporal cortex at early stages of Alzheimer's disease pathology. (21st February 2018) - Alonso‐Andrés, Patricia; Albasanz, José Luis; Ferrer, Isidro; Martín, Mairena
Abstract: Adenosine, hypoxanthine, xanthine, guanosine and inosine levels were assessed by HPLC, and the activity of related enzymes 5′‐nucleotidase (5′‐NT), adenosine deaminase (ADA) and purine nucleoside phosphorylase (PNP) measured in frontal (FC), parietal (PC) and temporal (TC) cortices at different stages of disease progression in Alzheimer's disease (AD) and in age‐matched controls. Significantly decreased levels of adenosine, guanosine, hypoxanthine and xanthine, and apparently less inosine, are found in FC from the early stages of AD; PC and TC show an opposing pattern, as adenosine, guanosine and inosine are significantly increased at least at determinate stages of AD whereas hypoxanthine and xanthine levels remain unaltered. 5′‐NT is reduced in membranes and cytosol in FC mainly at early stages but not in PC, and only at advanced stages in cytosol in TC. ADA activity is decreased in AD when considered as a whole but increased at early stages in TC. Finally, PNP activity is increased only in TC at early stages. Purine metabolism alterations occur at early stages of AD independently of neurofibrillary tangles and β‐amyloid plaques. Alterations are stage dependent and region dependent, the latter showing opposite patterns in FC compared with PC and TC. Adenosine is the most affected of the assessed purines.